PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN PADA PERUSAHAN DAERAH AIR MINUM (PDAM) KABUPATEN KEDIRI - Rosalinda, Nike Ana; Subagyo, Subagyo; Bhirawa, Sigit Wisnu Setya (Universitas Nusantara PGRI Kediri, 2022)
In general, this study aims to determine the impact style of leadership , work environment, and OCB (Organizational Citizenship Behavior) in PDAM Kediri Regency employee performance, a type of causality study. The sample obtained by PDAM Kabupaten Kediri for this study was a random sample of 40 from the general population, conducted by random sampling. Collect data using questionnaires analyzed using multiple regression analysis. The results show that leadership style, work environment, and Organizational Citizenship Behavior (OCB) partially and simultaneously significantly perfomance employee of influence.